Produtividade, estabilidade e adaptabilidade em progênies de Myracrodruon urundeuva F.F. & M.F. Allemão – Anacardiaceae - Sebbenn, Alexandre Magno; Silva, Alexandre Marques [UNESP]; de Moraes, Marcela Aparecida [UNESP]; Resende, Marcos Deon Vilela; Freitas, Miguel Luiz Menezes; De Moraes, Mario Luiz Teixeira [UNESP]; Valerio Filho, Walter Veriano [UNESP]; Manoel, Ricardo de Oliveira [UNESP] (Ipef-inst Pesquisas Estudos Florestais, 2012)
The use and inadequate exploitation of natural resources is restricting the occurrence of aroeira (Myracrodruon urundeuva F.F. & M.F. Allemão), which now is on the FAO list of endangered species. This exploitation causes a decrease in the genetic base of M. urundeuva populations, which makes it difficult to find genotypes with stability and adaptability to different growing conditions. This study aimed at estimating the genetic variation and productivity, stability and adaptability of progenies of a M. urundeuva natural population, from the Ecological Station of Paulo de Faria-SP, under different planting systems. DBH (diameter at breast height) was evaluated in four progeny tests of M. urundeuva: i) planted with Anandenanthera falcata and Guazuma ulmifolia (TP-AMA); ii) single (TP-ASO); iii) planted with annual crops (TP-SAF) and iv) planted with Corymbia citriodora (TP-EUCA), installed in Selvíria-MS. The experimental design consisted of complete randomized blocks with three replications and a variable number of plants per plot in each of the four planting systems. From the joint analysis of the planting systems studied, it was found that: i) there were variations among planting systems particularly in TP-SAF; ii) only in TP-EUCA it was possible to detect variations among the progenies; iii) the effects of the genotype x environment interaction were not significant. Thereby, the harmonic mean of genotypic values (MHVG), the relative performance of genotypic values from the mean of each site (PRVG) and the harmonic mean of the relative performance of genotypic values (MHPRVG) for DBH showed, respectively: progenies with greater stability, adaptability, and stability and simultaneous adaptability within different planting systems. The use of these selection criteria provided a more refined selection of the best progenies of M. urundeuva under the different planting systems studied.
Productive, stability and adaptability in progenies of Myracrodruon urundeuva FF & M.F. Allemao - Anacardiaceae
Keywords: Genetic adaptability; Genetic base; Genetic stability; Productivity valo; Corymbia; Diameter-at-breast heights; Endangered species; Genetic variation; Genotype x environment interaction; Growing conditions; Guazuma ulmifolia; Harmonic mean; Joint analysis; Natural population; Planting systems; Progeny tests; Relative performance; Selection criteria; Selection of the best; Variable number; Conservation; Genes; Plants (botany); Productivity; System stability